C–C Cross‐Coupling Reactions of Organosilanes with Terminal Alkenes and Allylic Acetates Using PdII Catalyst Supported on Starch Coated Magnetic Nanoparticles. Issue 7 (6th February 2020) - Patra, Debabrata; Panja, Subir; Saha, Amit
Abstract : Starch coated magnetic nanoparticles supported palladium catalyst has been explored to perform C–C cross coupling reactions, such as oxidative Heck coupling and Tsuji–Trost allylic coupling using organosilicon compounds as one of the coupling partners. The biopolymer coated magnetic catalyst was very easy to recover magnetically and was efficiently recycled in the subsequent batches. All the reactions were performed in air and thus the necessity of air and moisture free reaction condition is avoided. The present protocols show wide substrate scope and good yields of the products. Abstract : Magnetically retrievable palladium nano‐catalyst has been used in oxidative Heck coupling and Tsuji–Trost allylic coupling reactions using organosilicon compounds as the aryl donors under air. The magnetic catalyst is easily recovered and efficiently recycled. Wide substrate scope and good yields of the products were obtained in both cases.